Focusing attention according to the HRP system and its relationship to the accuracy of peaceful shooting for Cubs basketball players - talal, mustafa; Refat, Luay (Journal of Physical Education, 2023)
This study aimed at identifying the degree of concentration of attention and its relationship peaceful scoring in basketball for Cubs players. The researchers used the descriptive approach due to the suitability of the objectives of the study, where the study sample consisted of (12) players from Alaadhamia club sport for ages under (14 years) for the year 2022-2023. They were chosen deliberately from research community represented by Baghdad club they have cubs players entrant in the Iraqi basketball association tournaments. were used the test of the concentration of attention in the system HRP , and the test of peaceful scoring in basketball , The study results showed a positive correlation between the degree of concentration of attention and peaceful scoring in basketball for Cubs players .Key words:  Attention focus, the system HRP, peaceful scoring in basketball.